The Creation of Dance Music "Seven Habits of Indonesian Children" As a Character Education Media - Sari, Ayu Titis Rukmana; Wahyudi, Wahyudi (JURNAL PENDIDIKAN DASAR NUSANTARA, 2025)
Character education is a crucial aspect in developing a young generation with integrity. One innovative approach to character education is through the performing arts, particularly dance music. This study aims to create a dance music piece called "Seven Habits of Indonesian Children" as a medium for character education in early childhood. Through an artistic approach and qualitative-descriptive methods, the creation process is carried out in four stages: exploration, improvisation, and evaluation. This study explores how elements of music and dance can be synergized to instill character values in children. The results show that dance music designed with educational aspects in mind can improve students' understanding and internalization of character values. This work has proven to be a fun, contextual, and effective learning medium in instilling character values through an aesthetic approach.